Program Pendampingan Peningkatan Literasi Bagi Siswa Sekolah Dasar - Melinda, Linda Daniati (LPPM POLITEKNIK LP3I, 2024)
This research was conducted to provide a solution to the lack of literacy among students in the primary school environment, especially in the learning process. Therefore, a programme is needed that can improve primary school reading skills through the implementation of a literacy programme. The purpose of this study is to find out the implementation of the literacy programme, the results of the literacy programme as well as the supporting and inhibiting factors of the implementation of the literacy programme in improving the reading skills of primary school students. This research is a qualitative research with descriptive method. The results obtained in this study show that the literacy programme is very important for primary school students in improving reading skills. The literacy activities include: literacy trees and corners, literacy clinics, smart flowers and library revitalisation. The obstacles in implementing the literacy programme are related to time and students' attitudes during learning.